A scoping review of female genital mutilation and its effects on sexual function and sexual satisfaction - Nusee, Zalina; Musa, Ramli; Ismail, Hamizah; Jamani, Nurjasmine Aida; Mohd Arifin, Siti Roshaidai; Mohd Zaki, Muhammad Aqlan; Abd. Aziz, Karimah Hanim; Yusof, Nurul Mutmainnah (IIUM Press, 2023)
The practice of female circumcision (FC), particularly female genital mutilation/cutting (FGM/C), has been controversial as it is regarded as physically and mentally harmful and violates human rights. The purpose of this study is to perform a scoping review aiming to evaluate and compare the effects of FC and FGM/C on the sexual function of the affected women, including the Google Scholar, EBSCO Discovery Service, PubMed, ProQuest Health & Medical Complete, and Wiley Online Library between the year 1999 to 2020. The following keywords were used: ‘Female Circumcision’, ‘Female Genital Mutilation, ‘Female Genital Cutting’, ‘Female Circumcision and Sexual Function’, and ‘Female Circumcision and Sexual Satisfaction. A total of 72 articles related to FC and sexual function or satisfaction were retrieved, and 30 articles met the inclusion criteria. Based on the analysis of the final 30 articles, most of the articles described the detrimental effects of FGM/C on sexual function and sexual satisfaction. However, future studies around the less invasive types of FGM/C are required to better reflect on FGM/C on female health. FGM is detrimental to female sexual satisfaction. However, a different method of FC that is less invasive may provide different outcomes. Therefore, a comprehensive guideline on proper FC techniques is needed for education among medical practitioners to prevent any adverse effects on sexuality.